Réponses

Meilleure réponse !
2014-09-20T03:43:24+02:00
A/ 5x^2-6x=x(5x-6)
b/ 3xy+x=x(3y+1)
c/ 2(x+1)^2-3 (x+1)=(x+1)(2x+2-3
=(x+1)(2x-1)
d/ (x+1)^2+x+1=(x+1)^2+(x+1)
=(x+1)(x+1+1)
=(x+1)(x+2)
exo50
(2x+1)^2-(1-x)^2
=(2x+1+1-×)(2x+1-1+x)
=(x+2)(3x)
b/ x^2-20x+100=(x-10)^2
c/ 25-(x+1)^2
=5^2-(x+1)^2
=(5+x+1)(5-×-1)
=(x+6)(-x+4)
d/ 4x^2+4+8x=4x^2+8x+4
=(2x+2)^2

exo 52
x^2-4+(x-2)(x+1)
=(x-2)(x+2)+(x-2)(x+1)
=(x-2)(x+2+x+1)
=(x-2)(2x+3)
b/ 3x^2-12x+12=3 (x^2-4x+4)
=3(x-2)
c/ x^2+3x+(x+3)^2
=x(x+3)+(x+3)^2
=(x+3)(x+x+3)
=(x+3)(2x+3)
d/ (x+1)(x+2)-(3x+6)
=(x+1)(x+2)-3 (x+2)
=(x+2)(x+1-3)
=(x+2)(x-2)